Chemical Profiling of the Street Drug Nyaope in South Africa using GC-MS. - E.M. Mwenesongole; P.M. Mthembi; M.D. Cole (Emerging Trends in Drugs, Addictions, and Health)
Introduction: Nyaope is a highly addictive low-grade heroin mixed with cannabis and/or other psychoactive compounds such as caffeine, lidocaine, phenacetin, dextromethorphan, and antiretroviral medication. The contents of Nyaope can differ within batches making it a challenge to profile. We present an analytical method for the storage, extraction, identification, and profiling of Nyaope. Methods: Identification and profiling of Nyaope was conducted with gas chromatography - mass spectrometry (GC-MS). Method validation parameters assessed were, stability, linearity, limits of detection and quantitation, accuracy and precision, ruggedness, selectivity, and recovery. Results: The method achieved accuracy of 80–120%, linearity with R2≥0.99, and precision values of less than 20%. Detection limits for diamorphine, efavirenz, nevirapine and Δ9-tetrahydrocannabinol ranged from 9.94 to 18.7 pg on column and the quantitation limits ranged from 30.1 to 56.6 pg on column. Stability, recoveries, and ruggedness were within acceptable laboratory standards. Samples were discriminated into original batches using the method and Principal Component Analysis and Hierarchical Clustering. Conclusions: The Southern African drug Nyaope can now be identified and compared. This can assist law enforcement agencies and public health stakeholders develop suitable methods to deal with supply and demand of this drug.